The Emperor Gratian on the battlefields (A.D. 367-383) (De Rebus Antiquis, 2021)
In this article, I analyze the image of the Western Roman Emperor Gratian as a warrior ruler. I hypothesize that the imperial victories were an element of legitimization of the power of this ruler who followed a long Greco-Roman tradition linked to the war. To confirm this assumption, the speeches made by the rhetorician Decimus Magnus Ausonius, Ambrose, the bishop of Milan, the pagan senator Quintus Aurelius Symmachus and the strategist Amianus Marcelinus, authors who were close to the emperor, were examined. To the analysis of these written documents, I added the examination of images engraved on two coins minted at the time of Gratian and that today are part of the collection of the Museu Histórico Nacional do Rio de Janeiro.
Keywords: Emperor Gratian; War; Legitimation of power; Written documents; Coins